Composite Systems Decisions - Levin, Mark Sh (Decision Engineering, 2006)
Composite decisions consist of interconnected parts or subdecisions and correspond to a composite (composable, modular, decomposable) system. The composite decision approach extends the traditional paradigm of decision making of Herbert A. Simon, i.e. choice of the best alternative(s), and realizes a two-stage solving scheme: (a) the selection of alternatives as the best subdecisions or local decisions and (b) composition of the selected local decisions into a composite global decision while taking into account the quality of the local decisions and their compatibility. Composite Systems Decisions describes an educational approach that is based on systems engineering and considered modular design of composite decisions. Divided into four parts, this book contains descriptions of basic systems approaches and examines basic 'technological' problems for composite systems, including: modular hierarchical design; multistage design; multistage planning; redesign/improvement/adaptation; evaluation; and, combinatorial evolution/development. Applied researchers, undergraduate and graduate students, and practitioners in many domains will find Composite Systems Decisions a valuable reference. The basic systems problems, solving schemes, and applied examples contained in the book will also be of interest to various scientists (e.g., mathematicians, computer scientists, economists, social engineers, etc.). The Decision Engineering series focuses on the foundations and applications of tools and techniques related to decision engineering, and identifies their relevance in 'engineering' decisions. The series provides an aid to practising professionals and applied researchers in the development of tools for informed operational and business decision making, within industry, by utilising distributed organisational knowledge.